Cognitive bias modification training of attention and interpretation to reduce expectations of social rejection in adolescents with eating disorders: A small efficacy randomized controlled trial. Issue 11 (22nd September 2022) - Rowlands, Katie; Beaty, Taryn; Simic, Mima; Grafton, Ben; Hirsch, Colette; Treasure, Janet; Cardi, Valentina
Abstract: Objective: This study aimed to investigate whether a computerized cognitive bias modification training delivered remotely would reduce expectations of rejection in adolescents with eating disorders. Method: Sixty‐seven adolescents aged 12–18 (99.5% female) with an eating disorder diagnosis (94% anorexia nervosa) and receiving specialist treatment were recruited. Participants were randomized to an intervention condition ( n  = 37) which included treatment as usual (TAU) supplemented by nine sessions of online cognitive bias modification training for social stimuli (CBMT + TAU), or a control condition ( n  = 30), which included TAU only. Participants were invited to complete assessments at baseline and post‐intervention. Results: In the intervention condition, 22/37 participants completed six or more training sessions and post‐intervention measures, the pre‐defined criteria to be considered "completers." In the control condition, 28/30 participants completed the post‐intervention measures. Participants who completed the intervention displayed a significantly greater reduction in negative interpretations of ambiguous social scenarios, with a medium effect size ( p  = .048, ηp2 = .090), and eating disorder psychopathology, with a medium effect size ( p  = .027, ηp2 = .105), compared to participants in the control condition. No significant between‐group differences were found on emotional response to criticism, and anxiety and depression symptoms post‐intervention ( p s > .05; small effect sizes). Discussion: Enhancing treatment as usual with CBMT targeting expectations of social rejection might be feasible and effective to reduce expectations of social rejection and eating disorder psychopathology in adolescents with eating disorders. Training adaptations might be necessary to impact on emotional processing and comorbid psychological distress. Public Significance: Adolescents with eating disorders who completed a brief (4‐week) online cognitive training intervention, alongside their usual treatment, reported greater reductions in expectations of social rejection and eating disorder psychopathology after the intervention, compared to a separate group of patients who received their usual treatment only. This brief and accessible intervention may be a helpful treatment adjunct for adolescents with eating disorders.